A Critical Review of Hyperloop (Ultra-High Speed Rail) Technology: Urban and Transport Planning, Technical, Environmental, Economic, and Human Considerations - Premsagar, Smriti; Kenworthy, Jeffrey (Frontiers in Sustainable Cities, 2022)
Companies globally have been trying to alter existing transportation systems to maximize public transport benefits, especially in the sector of high-speed (HS) ground transportation. The latest invention of such is Elon Musk's ultra-high-speed rail (UHSR), hyperloop. This technology enables a rail service to operate at a potential speed of 1,200 km/h. Hyperloop's ambitious speed goal has the potential to result in time-space shrinkage, which would then make distant cities more accessible with greatly reduced travel times. Since 2013, several companies have been vigorously promoting hyperloop development in various locations worldwide and competing to construct the world's first functional and commercially viable hyperloop. India, a country struggling with existing public transportation and urban mobility needs, agreed to construct a hyperloop through the company “Virgin Hyperloop One.” This paper first investigates the key technical, environmental, economic and human considerations in assessing the applicability of hyperloop to a particular location. It also considers in some detail the likely urban and regional planning and transport policy implications of the hyperloop technology based on the known effects of existing high-speed rail (HSR) systems. The paper concludes that many of the claims about hyperloop are subject to contrary information, meaning that great caution and prudence are currently needed regarding attempts at commercial deployment.